The effect of protective eyewear on free throw performance in basketball players without refractive defects - Şinasi Özsaydı; Ali Keleş; Banu Kabak; Gökhan Deliceoğlu (Pedagogy of Health)
Background and Study Aim. Sports-related eye injuries are a significant concern, particularly in high-risk activities such as basketball, where protective measures are often necessary. Protective eyewear is designed to prevent injuries, but its potential impact on athletic performance remains unclear. This study aimed to evaluate the effect of wearing protective eyewear on shooting performance in basketball athletes without refractive errors.